Delivery of fluorescent-labeled cyclodextrin by liposomes: role of transferrin modification and phosphatidylcholine composition. (2nd January 2017) - Chen, Jun; Yao, Junhong; Ma, Zhuyue; Peng, Pei; Lu, Shanshan; Hu, Yudong; Xu, Fei; Yang, Yang; Yang, Xixiong
Abstract: Drug-in-CD-in-liposome (DCL) systems which encapsulate the drug/CD inclusion complexes into inner aqueous phase of liposomes have been applied as a novel strategy to improve efficacy of lipophilic antitumor drugs. The aim of this work was to assess the role of transferrin (Tf) modification and phosphatidylcholine (PC) composition on the properties of liposomes containing hydroxypropyl-β-cyclodextrin (HP-β-CD). Fluorescence dye, FITC, was conjugated with HP-β-CD to facilitate the analysis. The resulting FITC-HP-β-CD was further encapsulated into liposomes and then the liposomes were modified with Tf. The FITC-HP-β-CD-loaded liposomes with different PC compositions were compared in terms of particle size, zeta potential, FITC content, FITC-HP-β-CD leakage, phase transition temperature ( T m ) and cellular uptake. The apparent partition coefficient values of different PCs were also determined. Compared to PEGylated liposomes, FITC-HP-β-CD-loaded liposomes modified with Tf had been proved to significantly increase vesicle stability and specific cellular uptake. Moreover, PC composition affected the properties of liposomes. Soybean phosphatidylcholine (SPC) liposomes modified with Tf were found to be more easily internalized into tumor cells than 1, 2-dipalmitoyl-sn-glycero-3-phosphatidylcholine (DPPC) and hydrogenated soybean phosphatidylcholine (HSPC) while Tf density on the liposomal surface was similar. And the lipophilicity of SPC was found to be much higher than DPPC and HSPC. Collectively, by the optimization of PC composition, the development of DCL modified with Tf might represent a potential strategy for the antitumor application of lipophilic drugs.